The Dynamic of Livelihood Recovery Program in Post Disaster Area: Challenges and Obstacles - Fiki Ferianto; Ilyas Lampe (Journal of Public Administration and Government, 2022)
Disasters cause most communities to lose their livelihoods and often place them in a more vulnerable condition. The government together with Non-Government Organizations (NGOs) are tackling these impacts through various Livelihood Recovery programs. However, little is known about how the program is run. This study aims to further explore how the dynamics of livelihood recovery programs in post-disaster areas. The method used is Mixed Methods where surveys, interviews and FGDs are conducted in data collection. This study found that the Cash Voucher Assistance (CVA) Program has been able to provide a source of livelihood for the beneficiaries, which is indicated by the fact that most of the businesses are still running. Switching business types and adding product types are beneficiary strategies to maintain their business. However, the weakness in building coordination with several government parties has led to the disintegration of the program which has an impact on further assistance. In addition, the program period, the quantity of beneficiaries and the human resources capacity of the program implementers have an impact on the quality of assistance provided.